Implikasi Hukum Terhadap Akta Perjanjian Kredit yang Dibuat Dengan Identitas Palsu (Studi Kasus Putusan Pengadilan Negeri Jakarta Barat Nomor 952/Pid.B/2019/Pn.Jkt.Brt.) - Prananda, Mayang Talentasari; Purba, Moses Frederick; Dafa, M Naufal Abiyi; Nurbaety, Setia Nanda; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses how to apply the principle of prudence in credit agreement deeds and the legal implications of credit agreement deeds made using false identities, with a case study of Decision Number 952/Pid.B/2019/PN.Jkt.Brt. The focus of the study lies in the application of the principle of prudence by banks and notaries in the process of making credit deeds. In this case, the debtor used a false identity to obtain credit, which then caused financial losses for the bank. The research method used in this study is a normative legal approach with secondary data. The results of the analysis show that identity falsification not only undermines the legal validity of credit deeds, but can also trigger criminal liability for notaries and administrative sanctions against banks. In addition, the application of the principle of prudence is important in providing credit and preventing losses for the bank as a creditor due to falsification of identity by the debtor.